The utility of routine head CT for hemorrhage surveillance in post-craniotomy patients undergoing anticoagulation for venous thromboembolism. (March 2021) - Hacker, Emily; Ozpinar, Alp; Fernandes, David; Agarwal, Nitin; Gross, Bradley A.; Alan, Nima
Highlights: Routine imaging during anticoagulation for VTE is common practice in neurosurgery. We detected subclinical intracranial hemorrhage in a small subset of patients. Temporary discontinuation of heparin drip resulted in fatal progression of VTE. Cessation of anticoagulation to manage subclinical hemorrhage may be precarious. Abstract: Anticoagulation for postoperative venous thromboembolism (VTE) may infer a higher risk of intracranial hemorrhage. We treat patients with VTE using slowly titrating intravenous heparin drip without bolus. When PTT is greater than 60 s, a head CT is obtained to monitor for the development of a intracranial hemorrhage before transition to oral anticoagulation. We evaluated the utility of routine surveillance head CT to monitor for intracranial hemorrhage during anticoagulation. This is a case series of neurosurgical patients in an academic quaternary hospital who developed a VTE after cranial procedures between 2007 and 2017. Over 11, 000 patients were screened for the study. Patients' demographics data, surgical indication, PTT at the time of surveillance CT head, surveillance CT head findings, and patient's clinical course were reviewed. A total of 83 patients were included. Three patients (3.6%) developed a new subclinical hemorrhage on CT head imaging while on heparin drip. Interval CT head showed stable hemorrhage in all patients. Heparin drip was stopped in two patients and they both progressed from DVT to pulmonary embolism: one patient died due to cardiac arrest, the other patient was transitioned to oral anticoagulation. In the third patient heparin drip was continued uneventfully and transitioned to oral anticoagulation with no further clinical sequalae. Surveillance CT while on heparin drip for VTE management detected subclinical intracranial hemorrhage in a small subset of patients. Patients whose anticoagulation was stopped had progression of VTE. Undertreatment of VTE in the presence of subclinical hemorrhage may lead to significant morbidity and mortality.